THE INFLUENCE OF HADITH ABOUT THE RIGHTS AND OBLIGATIONS OF HUSBAND AND WIFE ON MUSLIM FAMILY HARMONY - Hasan Ayatullah Asy'ari, Emha; Ikhsan Silviantoro, Noor; Tujang, Bisri (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to analyze the influence of the hadith about the rights and duties of husband and wife on the harmony of Muslim families. In Islam, the family is a fundamental institution based on love, affection, and responsibility. Hadiths of the Prophet Muhammad provide guidance on the rights and obligations of husband and wife to create a harmonious and balanced household. This study examines the extent to which the understanding and application of these traditions contribute to the quality of relationships in Muslim families. The approach used in this study is quantitative correlational, with the Stratified Random Sampling method in sampling from Muslim families in Jember. Data were collected through interviews, observation, documentation, and questionnaires measuring the level of hadith understanding and family harmony based on aspects of communication, husband's leadership, wife's role, and couple's emotional well-being. Data were analyzed by Pearson Product Moment correlation test using SPSS version 26.0 for Windows to measure the relationship between the variables of hadith comprehension (X) and family harmony (Y). The results showed that there is a significant positive relationship between the understanding of hadith about the rights and obligations of husband and wife and the level of Muslim family harmony. The higher the understanding and application of hadith in the household, the better the level of communication, conflict management, and psychological well-being in the family. This study confirms that Islamic teachings on the rights and obligations of husband and wife have relevance in building a harmonious and stable household life.